1985
DOI: 10.1161/01.atv.5.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Postheparin plasma triglyceride lipases. Relationships with very low density lipoprotein triglyceride and high density lipoprotein2 cholesterol.

Abstract: Hepatic triglyceride lipase (HTGL) and lipoprotein lipase (LPL) probably have major roles in the removal of triglyceride from triglyceride-rich lipoproteins and in the formation of high density lipoprotein (HDL). However, no population-based study of their activity and relationship to lipoprotein lipid levels has been reported. To determine these relationships, we recalled 33 men and 17 women of a randomly selected sample of the Lipid Research Clinics Pacific Northwest Bell Telephone Company Health Survey. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
37
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 36 publications
9
37
1
Order By: Relevance
“…However, results of our multivariate analyses revealed that with the exception of plasma HDL cholesterol levels, which were characterized by a significant sex effect, differences in the plasma lipid profile between men and women were largely explained by differences in visceral AT and PH-LPL activity. In addition to the variation in lipoprotein-lipid levels between men and women, a significant sex difference in PHLA was also found, a finding that is concordant with several, [35][36][37][38] but not all, 39,40 previous reports.…”
Section: Effect Of Sexsupporting
confidence: 90%
“…However, results of our multivariate analyses revealed that with the exception of plasma HDL cholesterol levels, which were characterized by a significant sex effect, differences in the plasma lipid profile between men and women were largely explained by differences in visceral AT and PH-LPL activity. In addition to the variation in lipoprotein-lipid levels between men and women, a significant sex difference in PHLA was also found, a finding that is concordant with several, [35][36][37][38] but not all, 39,40 previous reports.…”
Section: Effect Of Sexsupporting
confidence: 90%
“…Thus, these results support the proposal that HDL 2 levels may be controlled by hepatic lipase. 36 ' 37 The significant con-elation between hepatic lipase and obesity in Pima women is consistent with previous studies. As in our previous study, 38 we did not observe sex differences in LPL in obese Pima men and women, although adipose LPL was higher in lean women compared to lean men.…”
Section: Llpase Activitiessupporting
confidence: 88%
“…This is consistent with the data from Caucasian populations. 35 " 37 In both sexes there was a strong negative association between hepatic lipase and HDI-2 concentrations. Thus, these results support the proposal that HDL 2 levels may be controlled by hepatic lipase.…”
Section: Llpase Activitiesmentioning
confidence: 96%
“…HL activity is elevated in males and postmenopausal women, both at increased risk for atherosclerosis. [13][14][15][16] In rabbits transgenic for human apoB, HL expression results in atherogenic small dense LDL particles. 17 In female apoE-deficient mice (an atherosclerosis model), atherosclerosis was reduced when the mouse (m) HL gene was deleted by gene targeting.…”
mentioning
confidence: 99%